# Algebra

posted by .

The only solution to sqrt (2x+3) - sqrt(x+1) = 1 is x = 3
I think that is true but I'm not sure if I was suppose to separate this equation I just put the 3 in the place of the x and it was true but should I have done it differently?

• Algebra -

The answer is 3 and -1, from Wolframealpha

I arrived at the - 1 answer, but not sure if the way I solved it is correct and just luck that I got the correct answer of -1!!

maybe a tutor will step in an answer.

• Algebra -

x = 3 does not satisfy the equation as a solution.
LS = (6+3) - √4
= 9-2
= 7
RS = 1
LS ≠ RS, so x ≠ 3

let's solve it ...
(2x+3) - sqrt(x+1) = 1
2x + 3 - 1 = √(x+1)
2x+2 = √(x+1)
square both sides
4x^2 + 8x + 4 = x+1
4x^2 + 7x + 3 = 0
(x+1)(4x+3) = 0
x = -1 or x = -3/4

if x = -1
LS = (-2+3) - √0
= 1-0 = 0
= RS

if x = -3/4
LS = 2(-3/4) + 3 - √(1/4)
= 3/2 - 1/2 = 1
= RS

so x = 0 or x = -3/4

• ARGHH! Algebra -

Just plain ol' did not see that first square root sign!

• 2nd try .... Algebra -

√(2x+3) = √(x+1) + 1
square both sides
2x+3 = x+1 + 2√(x+1) + 1
x + 1 = 2√(x+1)
square again ...
x^2 + 2x + 1 = 4(x+1)
x^2 - 2x - 3 = 0
(x+1)(x-3) = 0
x = -1 or x = 3

checking both,since we squared.

if x = -1
LS = √(-2+3) - √0
= √1-√0 = 1 = RS

if x = 3
LS = √9 - √4
= 3-2
= 1 = RS

So x = -1 or x = 3

## Similar Questions

1. ### Inequality

When I solve the inquality 2x^2 - 6 < 0, I get x < + or - sqrt(3) So how do I write the solution?
2. ### math,algebra,help

Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
3. ### some algebra help (radicals)

I hope I am writing this down right.. I am trying to do some practice questions to learn 10^5 (sqrt)2y - 4^5 (sqrt)2y I am trying to figure out how to solve this They gave us some answers to choose from, but I am clueless on how to …

Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
5. ### Algebra 2

Operations with Complex Numbers Simplify. 1. sqrt(-144) 2. sqrt(-64x^4) 3. sqrt(-13)*sqrt(-26) 4. (-2i)(-6i)(4i) 5. i13 6. i38 7. (5 – 2i) + (4 + 4i) 8. (3 – 4i) – (1 – 4i) 9. (3 + 4i)(3 – 4i) 10. (6 – 2i)(1 + i) 11. (4i)/(3+i) …
6. ### algebra

Simplify: ( sqrt (2) + sqrt (3) ) ( sqrt (2) - sqrt (3) )?
7. ### Algebra

I have a question if someone could help, please explain it. Given b = -1 and h = -1, what is the equation of the graph if the parent function is y = sqrt (x) Answers: a.y = sqrt(x-1) b.y = sqrt (-x+1) c.y = - sqrt (-x-1) d.y = sqrt(-x-1) …
8. ### Algebra

Could you please check my answers and help with the ones I can't figure out- 1. Solution to the radical function sqrt(12x+1) = 1 is x = 0 True or False I think it is true according to my calculations 2.Solve x = sqrt(8x) 8x = x^2 x^2 …
9. ### Algebra-Please check my calculations

Could you please check my answers and help with the ones I can't figure out- 1. Solution to the radical function sqrt(1/2x+1) = 1 is x = 0 True or False I think it is true according to my calculations 2.Solve x = sqrt(8x) 8x = x^2 …
10. ### Algebra

Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work. sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2) x*sqrt 7x-49*x ^^^ would this be my final answer?

More Similar Questions